Urban Community Forestry in Nepal: A Case Study of the Ranibari Community Forest in Kathmandu - Sapkota, Sushant; Bhattarai, Rudra Prasad; Khadka, Bimal Kumar (International Research Journal of Parroha, 2025)
Community forestry was introduced in Nepal in the late 1970s to empower local communities in managing natural resources. While its success in rural areas is well-documented, its role in urban settings remains underexplored. This study examines the impact of community forestry on the social, environmental, and economic dimensions of urban life, focusing on the Ranibari Community Forest in Kathmandu. A mixed-methods approach was employed, integrating qualitative interviews, quantitative surveys, and systematic observations to analyze how urban residents engage with the community forest and its contribution to urban resilience. Findings demonstrate that the Ranibari Community Forest significantly enhances environmental quality, fosters social cohesion, and generates economic benefits for city residents. However, challenges persist due to rapid urbanization, evolving policies, and management complexities. The study highlights the critical importance of incorporating community forestry into urban planning frameworks to promote sustainable development and resilience in urban areas.